폐쇄성수면무호흡증후군 선별을 위한 소아용 수면설문지 - 강은경 (Allergy asthma & respiratory disease, 2019)
Obstructive sleep apnea syndrome (OSAS) is the most severe form of obstructive sleep-disordered breathing. It can produce cardiovascular problems, growth retardation, cognitive deficits, and behavioral problems such as attention deficit/hyperactivity symptoms in children. The diagnostic gold standard for OSAS is overnight polysomnography, but it is expensive, time-consuming, and labor intensive, and is conducted by specialized centers which have trained personnel. Therefore, sleep questionnaires as screening tools for OSAS was developed. The benefits of sleep questionnaires are easy/quick application and low cost. The objective of this review is to describe several available pediatric sleep questionnaires which are helpful in screening OSAS. KCI Citation Count: 0